Procedure‐specific simulation for vaginal surgery training: A randomized controlled trial - Roxana Geoffrion; Nicole A. Koenig; Geoffrey W. Cundiff; Catherine Flood; Momoe T. Hyakutake; Jane Schulz; Erin A. Brennand; Terry Lee; Joel Singer; Nicole J. Todd (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Vaginal surgery has a superior outcome profile compared with other surgical routes, yet skills are declining because of low case volumes. Graduating residents' confidence and preparedness for vaginal surgery has plummeted in the past decade. The objective of the present study was to investigate whether procedure‐specific simulation skills, vs usual training, result in improved operative competence. Material and methods We completed a randomized controlled trial of didactic and procedural training via low fidelity vaginal surgery models for anterior repair, posterior repair (PR), vaginal hysterectomy (VH), recruiting novice gynecology residents at three academic centers. We evaluated performance via global rating scale (GRS) in the real operating room and for corresponding procedures by attending surgeon blinded to group. Prespecified secondary outcomes included procedural steps knowledge, overall performance, satisfaction, self‐confidence and intraoperative parameters. A priori sample size estimated 50 residents (20% absolute difference in GRS score, 25% SD, 80% power, alpha 0.05). Clinicaltrials.gov: Registration no. NCT05887570. Results We randomized 83 residents to intervention or control and 55 completed the trial (2011–23). Baseline characteristics were similar, except for more fourth‐year control residents. After adjustment of confounders (age, level, baseline knowledge), GRS scores showed significant differences overall (mean difference 8.2; 95% confidence interval [CI]: 0.2–16.1; p = 0.044) and for VH (mean difference 12.0; 95% CI: 1.8–22.3; p = 0.02). The intervention group had significantly higher procedural steps knowledge and self‐confidence for VH and/or PR (p < 0.05, adjusted analysis). Estimated blood loss, operative time and complications were similar between groups. Conclusions Compared to usual training, procedure‐specific didactic and low fidelity simulation modules for vaginal surgery resulted in significant improvements in operative performance and several other skill parameters.